Litter size in gilts after altrenogest and flushing - Duane L Davis; Jeffrey S Stevenson; D S Pollmann; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1984)
Effects of estrous synchronization and flushing on litter size in gilts were compared on two farms. Estrus in gilts was synchronized with altrenogest for 14 days or estrous cycles were left unaltered (control group). One-half of the synchronized gilts were flushed by feeding supplemental ground milo (3.4 lb) in addition to 4 lb of a basal milo-soybean meal diet that all gilts received. Additional milo was provided from day 8 of altrenogest treatment until the first day of estrus. Response on the two farms differed. Altrenogest-treated gilts from one farm farrowed about one more pig than controls, regardless of whether they were flushed or not. On the second farm, litter size for control and altrenogest-treated gilts was similar but gilts that received both altrenogest and additional milo (flushed) farrowed about 1.5 more pigs. Reasons for farm differences are unknown but could be related to differing genetic background and farm environment of the gilts studied.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Litter size; Gilts; Altrenogest; Flushing